GUIDELINES FOR DEVELOPING THE CHARACTERISTICS OF ADMINISTRATORS OF HIGHLAND EDUCATIONAL INSTITUTIONS IN REMOTE AREAS YOD DOI EDUCATIONAL QUALITY DEVENLOPMENT NETWORK DISTRICT OF THE CHIANGMAI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 5 - Deeu-Mong, Khamolkarn; Yuttawong, Nolthawat; Saengseemuk, Suraphong (Journal of MCU Nakhondhat, 2024)
The purposes of this research are to 1) Study the characteristics of administrators of highland educational institutions in remote areas Yoddoi educational quality development network under the district of the Chiang Mai primary educational service area office 5 and 2) Find guidelines for developing the characteristics of administrators of highland educational institutions in remote areas Yoddoi educational quality development network under the district of the Chiang Mai primary educational service area office 5, Using a mixed methods research method. The target group is there were 63 teachers in educational institutions of the Yoddoi educational quality development network and 9 qualified informants. Data were collected using questionnaires and structured interviews. Data were analyzed by finding frequencies, percentages, means, standard deviations. and content analysis. The results of the research found that: Characteristics of administrators of highland educational institutions in remote areas Yoddoi educational quality development network. Overall is at a high level ( = 4.19, S.D. = 0.30). Arranged from highest to lowest is knowledge and abilities is the highest, followed by personality Human relations, morality and ethics and leadership is the lowest, respectively. Guidelines for developing the characteristics of administrators of highland educational institutions in remote areas Yoddoi educational quality development network personality educational institution administrators should have thought leadership in solving operational problems reasonably. Be honest with yourself and others. Morality and ethics be honest and perform your duties with transparency and openness. Knowledge and abilities be a leader in bringing teachers and all stakeholders together to analyze the school environment in order to set a vision, policy, and goals. Human relations be friendly and have good human relations. And leadership use be professional learning community group activities to promote teachers' participation in school administration.